790 A phase II study (TACTI-002) of eftilagimod alpha (a soluble LAG-3 protein) with pembrolizumab in PD-L1 unselected patients with metastatic non-small cell lung(NSCLC) or head and neck carcinoma(HNSCC). (10th December 2020) - Krebs, Matthew; Majem, Margarita; Felip, Enriqueta; Forster, Martin; Doger, Bernard; Clay, Tim; Carcereny, Enric; Peguero, Julio; Horn, Leora; Bajaj, Pawan; Roxburgh, Patricia; Brignone, Chrystelle; et al.
Abstract : Background: Eftilagimod alpha (efti) is a soluble LAG-3 protein that binds to a subset of MHC class II molecules to mediate antigen presenting cell (APC) and CD8 T-cell activation. The stimulation of the dendritic cell network and subsequent T cell recruitment may lead to stronger anti-tumor responses in combination with pembrolizumab than observed with pembrolizumab alone. We report results from stage 1 of all parts of the study (NCT03625323 ). Methods: Patients (pts) with unselected PD-L1 expression were recruited into 3 cohorts: part A; 1st line, immunotherapy naïve NSCLC; part B; 2nd line, immunotherapy refractory NSCLC and part C; 2nd line immunotherapy naive HNSCC. The study uses a Simon's 2-stage design, with objective response rate (ORR) by iRECIST as the primary endpoint (EP). Secondary EPs include tolerability, disease control rate (DCR), progression free survival (PFS), overall survival (OS), PK, PD and immunogenicity. Fifty-eight (58) pts were recruited into stage 1. Up to additional 51 pts will be recruited if a pre-specified ORR threshold is met for the respective part. Efti is administered as 30 mg subcutaneous injection every 2 wks for 8 cycles and then every 3 wks for 9 cycles; pembrolizumab is administered at 200 mg intravenous infusion every 3 wks for up to 2 yrs. The study was approved by ethic committees and institutional review boards. Results: Between Mar 2019 and Jul 2020 88 pts were enrolled. The median age was 67 yrs (range 53-84) and 70% were male. ECOG PS 0:1 was 42% and 58% respectively. Pts from all PD-L1 tumor expression subgroups were recruited. Pts received a median of 4 (1-25) pembrolizumab and 5.5 (1-22) efti administrations. The most common (≥ 15%) treatment emergent adverse events (TEAEs) were asthenia (28%), cough (27%), decreased appetite (22%), dyspnea (21%), fatigue (18%) and diarrhea (15%). Three (3) pts discontinued due to treatment related AEs. The ORR (acc. to iRECIST) of the 58 patients enrolled into stage 1 is shown in (table1). PK profiles after the first or repeated efti dosing were in line with previous studies, with a mean Cmax at7 ng/ml reached ≤ 24h. Circulating TH1 biomarkers 2 weeks after the last efti administration were increased (3 months vs. baseline) by a mean 61% and 209% for CXCL10 (Student paired t-test, p=0.02, n=31) and IFN-γ(p= 0.02, n=19), respectively. Conclusions: Efti plus pembrolizumab is safe and shows encouraging antitumor responses in NSCLC and HNSCC patients Trial Registration: NCT03625323 Ethics Approval: The study was approved by relevant ethic committees and institutional review boards.